Analysis of the elastic bending characteristics of cementless short hip stems considering the valgus alignment of the prosthetic stem. (February 2018) - Jahnke, Alexander; Fonseca Ulloa, Carlos A.; Seeger, Jörn Bengt; Rickert, Markus; Jahnke, Gerhard Walter; Ahmed, Gafar Adam; Ishaque, Bernd Alexander
Abstract: Background: The resultant hip force causes a varus torque which must be compensated by a shear force couple depending on the stem alignment of the prosthesis. Since the prosthesis is substantially less flexible than the bone, the interior of the femur is stiffened over the entire prosthesis length. The present study thus aims at analyzing short-stem prostheses for its elastic bending characteristics, considering inappropriate valgus alignment of the prosthetic stem. Methods: Five short stem prostheses were implanted each in synthetic femora in a standardized manner – in neutral and valgus stem alignments. Bending movements were recorded applying a tilting torque MX of ±3.5 Nm in medio-lateral direction. Variance analyses and Friedman tests were used. A P-value <.05 was considered statistically significant. Findings: Bending movements b1 -b6 showed significant differences (P < .05). It could be shown that different stem alignments (P < .05) and different measuring points had a highly significant influence (P < .001) on the relative movements. Compared to the AIDA®, the MiniHip™ as well as the Metha® stiffened the femur to a higher degree (P < .001). Interpretation: Regarding the elastic bending behavior we see a relevant influence of the stems´ design. We conclude that the short-stem principle does not necessarily require the shortest possible prosthesis but rather a long and thin extending stem tip to optimize the lever ratios, ensuring a more physiological bending behavior of the femur. In addition, without sufficient anchoring of the prosthesis, the valgus stem alignment could favor tilting of the implant and should therefore be avoided. Highlights: The hip force causes a varus torque which must be compensated by the prosthesis. The femur is stiffened over the entire stem length. Stem alignment seems to have only a slight effect on the femoral bending. Short stem prosthesis should have a long, thin and flexible stem tip.